Mutations causing DOK7 congenital myasthenia ablate functional motifs in Dok-7. - Hamuro, J; Higuchi, O; Okada, K; Ueno, M; Iemura, S; Natsume, T; Spearman, H; Beeson, D; Yamanashi, Y (2008)
Dok-7 is a cytoplasmic activator of muscle-specific receptor-tyrosine kinase (MuSK). Both Dok-7 and MuSK are required for neuromuscular synaptogenesis. Mutations in DOK7 underlie a congenital myasthenic syndrome (CMS) associated with small and simplified neuromuscular synapses likely due to impaired Dok-7/MuSK signaling. The overwhelming majority of patients with DOK7 CMS have at least one allele with a frameshift mutation that causes a truncation in the COOH-terminal region of Dok-7 and affects MuSK activation. Dok-7 has pleckstrin homology (PH) and phosphotyrosine binding (PTB) domains in the NH2-terminal moiety, both of which are indispensable for MuSK activation in myotubes, but little is known about additional functional elements. Here, we identify a chromosome region maintenance 1-dependent nuclear export signal (NES) in the COOH-terminal moiety and demonstrate that the NES-mediated cytoplasmic location of Dok-7 is essential for regulating the interaction with MuSK in myotubes. The NH2-terminal PH domain is responsible for the nuclear import of Dok-7. We also show that the Src homology 2 target motifs in the COOH-terminal moiety of Dok-7 are active and crucial for MuSK activation in myotubes. In addition, CMS-associated missense mutations found in the PH or PTB domain inactivate Dok-7. Together, these findings demonstrate that, in addition to the NH2-terminal PH and PTB domains, the COOH-terminal NES and Src homology 2 target motifs play key roles in Dok-7/MuSK signaling for neuromuscular synaptogenesis. Ablation or disruption of these functional elements in Dok-7 probably underlies the neuromuscular junction synaptopathy observed in DOK7 CMS.